Core outcome set for pulmonary rehabilitation of people with COPD - Miranda, Sara Palos Souto de (2023)
This thesis defined a core outcome set - a minimum set of outcomes that should always be measured and reported – for pulmonary rehabilitation of people with chronic obstructive pulmonary disease (COPD). These core outcomes can increase study comparability and therefore enable drawing robust conclusions regarding the effects of this intervention. Furthermore, together with other indicators, the core outcome set might also enable benchmarking pulmonary rehabilitation and ensure quality of programmes delivered to people with COPD. Other potential benefits of establishing a minimum set of assessments (the work embedded in this thesis), are the increase in transparency of results to patients, pulmonary rehabilitation centres and payers, and the better understanding of patient responses to this therapy. This thesis combined both quantitative and qualitative research methods and had an active involvement of different stakeholders, such as people with COPD, informal caregivers, healthcare professionals, researchers and policy makers.